Effects of Emotion and Emotional Valence on the Neural Correlates of Episodic Memory Search and Elaboration - Ford, Jaclyn H. (J Cogn Neurosci, 2013)
Successful retrieval of an event includes an initial search phase in which the information is accessed and a subsequent elaboration phase in which an individual expands on event details. Traditionally, functional neuroimaging studies examining episodic memory retrieval either have not made a distinction between these two phases or have focused on the initial search process. The current study used an extended retrieval trial to compare the neural correlates of search and elaboration and to examine the effects of emotion on each phase. Prior to scanning, participants encoded positive, negative, and neutral images paired with neutral titles. After a thirty-minute delay, participants engaged in a scanned recognition task in which they viewed the neutral titles and indicated whether the title had been presented with an image during the study phase. Retrieval was divided into an initial memory search and a subsequent five-second elaboration phase. The current study identified neural differences between the search and elaboration phases, with search being associated with widespread bilateral activations across the entire cortex and elaboration primarily being associated with increased activity in the medial prefrontal cortex. The emotionality of the retrieval target was more influential during search relative to elaboration. However, valence influenced when the effect of emotion was greatest, with search engaging many more regions for positive events than negative ones, but elaboration engaging the dorsomedial prefrontal cortex more for negative events than positive events.